Metabolites Identification of Bioactive Compounds Daturataturin A, Daturametelin I, N-Trans-Feruloyltyramine, and Cannabisin F From the Seeds of Datura metel in Rats - Xu, Silun; Liu, Yan; Xiang, Ling; Zhou, Fan; Li, Hongyu; Su, Yongjian; Xu, Xinyi; Wang, Qi (Frontiers in Pharmacology, 2018)
Datura metel L. is a widely used traditional herbal medicine, and withanolides and amides are the two groups of main bioactive constituents in Datura metel seeds. This study aims to elucidate the metabolism of four representative bioactive compositions containing daturataturin A (1), daturametelin I (2), N-trans-feruloyltyramine (3), and cannabisin F (4) in rats. After separately oral administration of 20 mg/kg withanolides (1, 2) and amides (3, 4) to rats, a total of 12, 24 and 21 metabolites were detected in the plasma, urine and fecal samples, respectively. Among them, three hydroxylated metabolites, 1-M3, 2-M2, and 3-M5, were detected in plasma and rat liver microsome incubation system in high abundance. Two metabolites of 1 and 2 were unambiguously identified by comparing with reference standards. Particularly, the methylated metabolite 27α-methoxy-(22R)-22,26-epoxy-27-[(β-D-glucopyranosyl)oxy]ergosta-2,4,6,24-tetraene-1,26-dione (daturametelin L) is a new compound. The withanolides could readily get hydroxylation or methylation metabolism. Meanwhile, the phase II metabolism (glucuronidation or sulfation) was the major reaction for the amides. This is the first study on in vivo metabolism of these active compounds in seeds of Datura metel.